Leveraging virtual trips in Google expeditions to elevate students’ social exploration - Parmaxi, Antigoni; Stylianou, Kostas; Zaphiris, Panayiotis (My University, 2017)
This paper reports on an exploratory case study on the use of Google Expeditions in the context of an intensive Greek language course for specific academic purposes. Google Expeditions are collections of linked virtual reality content that can enable teachers to bring students on virtual trips to places like museums, human anatomy, surgical processes etc. Thematic analysis of instructors’ field notes, students’ reflections, interviews and focus group was employed aiming at identifying the potential of Google Expeditions for extending the language classroom through virtual trips. The use of Google Expeditions enabled students to extend the borders of the classroom by making virtual walkthroughs in places that would normally be unreachable and trigger social exploration through inter- and extra-VR communication, sharing of ideas, concepts and experiences. This study acts as a pilot with an eye to inform larger-scale investigation of Google Expeditions in the future. © IFIP International Federation for Information Processing 2017.
Keywords: Computer-assisted language learning; Constructionism; Social constructionism; Wearables